Analisis Efektivitas Pengendalian Internal: Deteksi Dini Fraud pada Pertanggungjawaban Keuangan PT. XYZ - Fernanda Putri Jelita; Ulfa Puspa Wanti Widodo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In Indonesia, recently there was fraud involving four companies with a total of Rp. 2.5 trillion. Fraud is an act that involves intentional cheating, deception, or manipulation to gain illegitimate gain or gain. This research aims to test the Analysis of Internal Control Effectiveness: Early Detection of Fraud on financial accountability PT. XYZ. Fraud in financial accountability in companies is a serious threat that can harm the company and its shareholders. The method used in the research is a qualitative descriptive method by conducting interviews and direct observation. The population of this research is employees in the Accounting and Finance Unit of PT. XYZ. The sample for this research is Verifier PT. XYZ. The result that can be concluded is that internal control can detect early fraud in financial accountability PT. XYZ.